Pelatihan dan Pengelolaan Teknologi Informasi Berkelanjutan dalam Peningkatan Pengembangan Desa Digital pada Bidang Pelayanan Publik dan Kearsipan di Gampong Reuleut Timur - Fakhrurrazi; Nurhafni; Ula, Mutammimul; Setiawan, Ade Luky; Arpika, Asma Mauli (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Information technology can improve the quality of information obtained by Gampong Reulet residents, especially in integrated public services and archives. Steps for Sustainable Information Technology Management in Improving Digital Village Development in the Field of Public Services and Archives include identifying village needs and potential, developing digital technology infrastructure, developing digital content and applications to support village needs in the archives sector. and public services, developing the skills and capacity of village communities in utilizing digital technology, as well as monitoring and evaluating the results of digital village development. The aim of the service is to provide Gampong Reuleut digital innovation to improve public services by utilizing technology to improve the performance of village officials and the efficiency of delivering information services. Second, digitizing archives can provide easy access and storage of information in several media so that the information is not lost. The results of this service increase administrative activities of gampong officials, provide comprehensive details about sustainable village operations, speed up services, and disseminate information related to gampong reulet including providing information services. Furthermore, the service has increased the development of digital villages, which shows that 90% and 10% of service participants feel quite satisfied with the implementation of service activities.